Management of congenital dysfibrinogenemia in pregnancy: A challenging patient case. Issue 8 (16th November 2021) - Langer, Megan; Manire, Meredith; Clarkson, Matthew; Samhouri, Yazan; Shah, Deep; Bhagavatula, Rama
Abstract: Afibrinogenemia and congenital dysfibrinogenemia (CD) are rare conditions with limited information available for appropriate management. Previous case reports have demonstrated the safe and efficacious use of fibrinogen replacement therapy (FRT) as a therapeutic approach to prevent hemorrhage and fetal loss in pregnant women with CD. In this case report, we present a 28‐year‐old pregnant woman who sought testing for CD given her family history. She denied any current or previous bleeding symptoms. Laboratory testing confirmed the diagnosis of CD. She was treated with FRT and prophylactic anticoagulation starting in her third trimester. She had preterm labor that prompted an urgent cesarean section with FRT support. This case adds to the sparse literature about fibrinogen disorders in pregnancy, and highlights the benefits, safety, and tolerability of FRT and prophylactic anticoagulation in pregnant women with CD. Finally, it emphasizes the importance of a multidisciplinary team approach for an uneventful delivery.